Dietary Antioxidants and Chronic Diseases - Małgorzata Elżbieta Zujko; Anna Maria Witkowska (MDPI AG, 2023)
Chronic diseases, most notably diabetes, cancer, cardiovascular diseases, neurodegenerative diseases, thyroid diseases, and allergic diseases are major causes of death, disability, and a lower quality of life in various populations [...]